The Impact Of Service Excellence And Customer Perceptions On The Success Of The Program Simpedes Hadiah Langsung At Bri Unit Ngrengket Kanca Nganjuk - Abdi Surya Muchlisin; Sriwahyuni Mega Hastuti (Universitas Islam Kadiri, 2022)
This study aims to determine the impact of service excellence and customer perceptions on the success of the Program Simpedes Hadiah Langsung at BRI Unit Ngrengket Kanca Nganjuk Unit. This research is quantitative-descriptive. The technique of sampling is saturated sampling. Saturated sampling is a sampling technique when all members of the population are used as samples. Therefore, the sample of this research is the Program Simpedes Hadiah Langsung Customers at Bank BRI Ngrengket Kanca Nganjuk Unit as many as 40 customers. The data collection techniques used are 1) Questionnaire and 2) Item Validity Test Documentation is done by using Product Moment correlation technique from Person. While the reliability test using Alpha Croanbach. The results of this study indicate that there is a simultaneous influence of service excellence and customer perceptions of the Program Simpedes Hadiah Langsung at BRI Bank Ngrengket Kanca Nganjuk Unit. Meanwhile, partially the success of the Program Simpedes Hadiah Langsung can be explained by the perception variable in Bank BRI Kanca Nganjuk customers. Service excellence at the BRI unit Ngrengket Kanca Nganjuk can be measured from each of the following indicators: Attitude, Attention, Action, Ability, Appearance, Accountability. For Customer Perception, it can be measured using each of the following indicators: Product Knowledge, Professionalism, Reputation. Meanwhile, the success of the Program Simpedes Hadiah Langsung can be measured using the following indicators: Increase in Balance, Increase of Customers, and Customer Loyalty.